Beispiel Nr: 08
$ \text{Gegeben:}\\\text{Länge} \qquad b \qquad [m] \\ \text{Diagonale} \qquad d \qquad [m] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad a \qquad [m] \\ \\ a = \sqrt{d^{2} -b^{2} }\\ \textbf{Gegeben:} \\ d=15m \qquad b=12m \qquad \\ \\ \textbf{Rechnung:} \\ a = \sqrt{d^{2} -b^{2} } \\ b=12m\\ d=15m\\ a = \sqrt{(15m)^{2} -(12m)^{2} }\\\\a=9m \\ \small \begin{array}{|l|} \hline d=\\ \hline 15 m \\ \hline 150 dm \\ \hline 1,5\cdot 10^{3} cm \\ \hline 1,5\cdot 10^{4} mm \\ \hline 1,5\cdot 10^{7} \mu m \\ \hline 0,015 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 12 m \\ \hline 120 dm \\ \hline 1,2\cdot 10^{3} cm \\ \hline 1,2\cdot 10^{4} mm \\ \hline 1,2\cdot 10^{7} \mu m \\ \hline 0,012 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline 9 m \\ \hline 90 dm \\ \hline 900 cm \\ \hline 9\cdot 10^{3} mm \\ \hline 9\cdot 10^{6} \mu m \\ \hline 0,009 km \\ \hline \end{array}\\$